Optimization of makerspace microfabrication techniques and materials for the realization of planar, 3D printed microelectrode arrays in under four days. Issue 16 (18th March 2019) - Kundu, Avra; Nattoo, Crystal; Fremgen, Sarah; Springer, Sandra; Ausaf, Tariq; Rajaraman, Swaminathan
Abstract : "Makerspace microfabrication" with the use of simple tools and materials is used to demonstrate the realization of 2D microelectrode arrays (MEAs) having a density of up to 8 × 8 MEAs in under four days which are comparable to conventional MEAs. Abstract : Conventional two-dimensional microelectrode arrays (2D MEAs) in the market involve long manufacturing timeframes, have cleanroom requirements, and need to be assembled from multiple parts to obtain the final packaged device. For MEAs to be "used and tossed", manufacturing has to be moved from the cleanroom to makerspaces. In order to enable makerspace fabricated MEAs comparable to conventional MEAs, the microfabrication processes must be optimized to have similar electrical properties along with biocompatibility and number of recording sites. This work presents a makerspace microfabricated 2D MEA having electrode densities up to a commercially popular 8 × 8 array, all fabricated under four days. Additive manufacturing-based realization of the MEA devices provides immense flexibility in terms of meeting distinct design requirements. A unique non-planar MEA having meso-scale electrodes on the top side of a chip transitioning to traces onto the bottom side through electrical vias is presented in this work. This allows for (a) monolithic integration of a culture well for devices having up to a 6 × 6 MEA array, (b) selective electroplating of the meso-scale electrodes (500 μm diameter) defined by silver ink casting followed by pulsed electroplating of gold or platinum without any masking procedure, (c) casting of a uniform and planar insulation layer via a novel process of confined precision spin coating (CPSC) of SU-8 which acts as a biocompatible insulation atop the meso-scale electrodes; and (d) selective laser micromachining to define the 50 μm × 50 μm microelectrodes. For an 8 × 8 array, the culture well and MEA chip framework are 3D printed as two separate parts and sealed together with a biocompatible epoxy as in commercially available MEAs. The fabricated MEAs have an average 1 kHz impedance of 36.8 kΩ/16 kΩ with a double layer capacitance of 400 nF cm −2 /520 nF cm −2 for nano-porous platinum/nano-gold which is comparable to the state-of-art commercially available 2D MEAs. Additionally, it was found out that our 3D printing-based process compares very favorably with traditional glass MEAs in terms of design to device while representing a dramatic reduction in cost, timeline for fabrication, reduction in the number of steps and the need for sophisticated microfabrication and packaging equipment.